Incorporating sustainable development principles into building design: a review from a structural perspective including case study. (30th July 2014) - Miller, Dane; Doh, Jeung‐Hwan
Summary: The incorporation of sustainable development (SD) principles into all industries is increasingly important. The contribution of the building industry to a wide range of environmental impacts is extensive with the construction, operation and maintenance of buildings accounting for approximately 50% of all energy usage and anthropogenic greenhouse gas (GHG) emissions globally. In the building design process, structural engineers play a limited role in the sustainability of a design. The decisions on the incorporation of such aspects are usually at the mercy of the architect and client. A literature review was conducted to record and present the variability in research on issues directly related to the environmental performance of structures. There are inconsistencies in the published contribution of embodied energy (EE) and proportion of life cycle energy usage in structures. Outcomes demonstrate that due to this variability, environmental performance of structures is difficult to validate. A systematic approach beginning with standardized calculation procedure and database generation for EE of building materials is essential for practitioners to deliver sustainable structural designs. An analysis of a typical concrete office structure indicates potential benefits through the use of quantifiable environmental performance measures, delivering efficient solutions. Comparisons of slab construction techniques indicate overall EE reductions up to 40% being achievable. Copyright © 2014 John Wiley & Sons, Ltd.